(untitled) (International Journal of Engineering and Computer Science, 2017)
The objective of designing this robot is simply to facilitate the humans in the future for security purposes. In the present scenario, there are many recent developments of robotics and communication on a large scale. The robot is in the form of a vehicle mounted with a web cam, which acquires and sends pictures PC. The movement of vehicle is controlled by microcontroller. Our idea is to make a robot to tackle the hostage situation &the worst conditions which cannot be handled by human being. Hence Humans are moved out from direct exposure to potentially dangerous situations. Robotic system can perform many security and surveillance functions more effectively than humans. The Keil micro software vision is used for writing Assembly level program code to the robot and for transferring the hex files to microcontroller.